The Effect of the Cooling Rate in the Cooling Process of Steel Materials on Hardness (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
This article discusses the theory of cooling steel materials. The article examines the effect of the cooling rate on the hardness of steel materials.